Peran Pendidikan Kewirausahaan dan Motivasi Berwirausaha dalam Mempengaruhi Minat Berwirausaha Mahasiswa - Didin Hikmah Perkasa; Fedri Triansah; Donant Alananto Iskandar (LITERATUS, 2020)
This research aims to determine the influence of entrepreneurship education and Entrepreneurial motivation to Entrepreneurship Interest in university students, the sampling in this study amounted to 66 respondents taken using technic total sampling. Methods of data analysis in this study using multiple linear regression analysis (SPSS 2.3). The results of this study show that entrepreneurship education variables have a positive and not significant impact on entrepreneurship interest of university students mercu buana faculty of economics and business regular 2 force year 2013 and variable of entrepreneurial motivation have positive and significant influence to Entrepreneurship Interest of university student mercu buana faculty of economics and business regular 2 force year 2013.